2000
DOI: 10.1046/j.1523-1755.2000.00207.x
|View full text |Cite
|
Sign up to set email alerts
|

Infection of mesangial cells with HIV and SIV: Identification of GPR1 as a coreceptor

Abstract: CD4 and GPR1 mRNAs were detected in mesangial cells. Mesangial cells were susceptible to HIV/SIV strains that use GPR1 as a coreceptor. Our findings suggest that an orphan G protein-coupled receptor, GPR1, is a coreceptor expressed in mesangial cells. It remains to be investigated whether the interaction of mesangial cells with specific HIV-1 strains through GPR1 plays a role in the development of HIVAN.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2001
2001
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 46 publications
0
21
0
Order By: Relevance
“…In 1992, Green et al [53] first showed that cultured renal mesangial cells could be infected by HIV-1. These findings were confirmed and expanded 8 years later by Tokizawa et al [54], who identified the chemokine receptor GPR1 as playing a critical role in this process, and by Conaldi et al [55], who found that the establishment of a persistent infection in these cells stimulates the synthesis of cytokines that could lead to glomerulosclerosis. In contrast, to date other investigators have been unable to infect cultured mesangial cells [56,57], and HIV-1 transcripts have not been found in mesangial cells from patients with HIVAN [58].…”
Section: Mesangial Hyperplasiamentioning
confidence: 68%
“…In 1992, Green et al [53] first showed that cultured renal mesangial cells could be infected by HIV-1. These findings were confirmed and expanded 8 years later by Tokizawa et al [54], who identified the chemokine receptor GPR1 as playing a critical role in this process, and by Conaldi et al [55], who found that the establishment of a persistent infection in these cells stimulates the synthesis of cytokines that could lead to glomerulosclerosis. In contrast, to date other investigators have been unable to infect cultured mesangial cells [56,57], and HIV-1 transcripts have not been found in mesangial cells from patients with HIVAN [58].…”
Section: Mesangial Hyperplasiamentioning
confidence: 68%
“…This observation raised the possibility that CCR2 might be involved in selective viral amplification in mucosal lymphocytes, the predominant site of replication during acute infection, but our results suggest that is not the case. In contrast, GPR1, GPR15, and APJ are not known to be expressed on CD4 Ï© T lymphocytes, although GPR1 is expressed on and reportedly supports in vitro HIV-1 infection of several nonlymphoid target cells (51,54). Within the genital tract, CCR2 and CCR3 are expressed in both female and male genital mucosa (36,41) although little is known about mucosal tissue expression of the other GPCRs used by HIV-1.…”
Section: Discussionmentioning
confidence: 99%
“…The etiology of HIV nephropathy is unclear, but there is evidence that direct infection of renal tubular and/or mesangial cells by HIV-1 may be a significant factor (18). It is also unclear why this disease afflicts principally African American men, but it is now the third most common etiology of endstage renal disease among African Americans aged 20 -64 years after diabetes and hypertension (17,19).…”
Section: Demand For Kidney Transplantationmentioning
confidence: 99%